From Accuracy to Fluency: The Synergy of Intensive and Extensive Reading in Arabic Language Education - AR, Mahmudi. (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines two principal approaches to developing Arabic reading skills (maharah al-qirah): intensive reading (al-qirah al-mukaththafah) and extensive reading (al-qirah al-muwassaah). Employing a qualitative methodology through a systematic literature review, the study analyzes 40 selected publications from 2015 to 2025 that discuss the concepts, characteristics, advantages, and limitations of each approach. Findings indicate that intensive reading enhances linguistic accuracy and analytical comprehension through detailed text analysis, whereas extensive reading promotes reading fluency, intrinsic motivation, and global comprehension through high-volume reading. The synthesis of findings yields an IntensiveExtensive Cycle model, beginning with detailed classroom analysis, followed by independent extensive reading, and concluding with integrative discussion. This model effectively combines reading accuracy and fluency. The study recommends that Arabic language teachers in Indonesia, particularly in madrasahs and pesantrens, integrate both approaches in a balanced manner.